2015
DOI: 10.1038/ng.3449
|View full text |Cite
|
Sign up to set email alerts
|

The primate-specific noncoding RNA HPAT5 regulates pluripotency during human preimplantation development and nuclear reprogramming

Abstract: Long intergenic noncoding RNAs (lincRNAs) are derived from thousands of loci in mammalian genomes and are frequently enriched in transposable elements (TEs). Although families of TE-derived lincRNAs have recently been implicated in the regulation of pluripotency, little is known of the specific functions of individual family members. Here we characterize three new individual TE-derived human lincRNAs, human pluripotency-associated transcripts 2, 3 and 5 (HPAT2, HPAT3 and HPAT5). Loss-of-function experiments in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(164 citation statements)
references
References 55 publications
6
158
0
Order By: Relevance
“…One strategy which ensures complete ablation would be to delete the entire genomic region associated with a lncRNA. For example, deletion of the 6kb lncRNA HPAT5 in pluripotent stem cells revealed a critical role for this lncRNA in pluripotency and primate preimplantation development [46]. This approach has been highly effective and expanded to create highly informative genome-wide scales of lncRNA depletion screens [47].…”
Section: Determining Function Using Genome and Epigenome Editing Toolsmentioning
confidence: 99%
“…One strategy which ensures complete ablation would be to delete the entire genomic region associated with a lncRNA. For example, deletion of the 6kb lncRNA HPAT5 in pluripotent stem cells revealed a critical role for this lncRNA in pluripotency and primate preimplantation development [46]. This approach has been highly effective and expanded to create highly informative genome-wide scales of lncRNA depletion screens [47].…”
Section: Determining Function Using Genome and Epigenome Editing Toolsmentioning
confidence: 99%
“…WDR5 itself needs the binding of specific lnc-RNAs essential to maintain this active chromatin state [123]. Recently, a primate-specific lnc-RNA HPAT5 was identified to be an integral regulator of pluripotency in preimplantation development [124]. Further untangling of the relationship of non-coding RNA and the epigenomic machinery will undoubtedly reveal detailed molecular mechanisms in species-specific function.…”
Section: Insights From the Interplay Of The Epigenome And Long Non-comentioning
confidence: 99%
“…For example, it has been reported that Sall4, Nanog, Esrrb, and Lin28 better recapitulated an ES expressional network than Oct4, Sox2, Klf4, and c-Myc [14]. Genomic-scale analyses have also shown that both miRs and large noncoding RNAs may interact with the reprogramming factors to enhance reprogramming [25,45,59]. Bioinformatic analysis has been utilized to investigate iPS reprogramming not only at the level of gene expression and transcription factor binding but also at the epigenetic level.…”
Section: Bioinformatic Analysis Of Induced Pluripotencymentioning
confidence: 99%